Comparison and Numeric Simulation of Two Sea Fog Processes behind High Pattern over Qiongzhou Strait - Wei YANG; Chunhua ZHANG; Xiao FENG; Xun LI; Jianxing LIN (Gaoyuan qixiang)
Using mesoscale numerical forecasting model WRF and National Centers for Environmental Prediction （NCEP） reanalysis data， two persistent sea fog events on 17-20 February 2018 and 4-6 February 2019 over Qiongzhou strait were simulated.Combined with visibility data of CMA Land Data Assimilation System， satellite and ground observations， the weather background， maintenance and development， water vapor transport， dynamic condition and cloud-fog structure of two sea fog processes were compared and analyzed.The results indicated that both persistent sea fog cases occurred at the back of denatured cold high moving in to the sea.During the 2018 sea fog events period， easterly water vapor convergence was strong， the high relative humidity in the lower layer was deep.The increasing relative humidity and strong water vapor convergence caused the advection fog last for more than 10 hours， with a minimum visibility of 100 m.Meanwhile， the mid-level cloud coexist with sea fog could reduce the shortwave radiation received by the ground in the daytime and weaken the warming effect， while played a role in heat preservation at night making surface-based lower temperature and inversion layer stability maintenance.Thus， the presence of clouds above the fog had a great effects on the maintenance and development of the lasting fog event.During the 2019 sea fog events period， the southeast water vapor convergence was weak， the high relative humidity was shallow， the sea fog with small area in Qiongzhou Strait developed first from inland， and dissipated after sunset.